2020
DOI: 10.1016/j.parepi.2020.e00173
|View full text |Cite
|
Sign up to set email alerts
|

Status of Anaplasma spp. infection in domestic ruminants from Iran: A systematic review with meta-analysis

Abstract: Anaplasma species are tick-borne pathogens that are obligatory intracellular of ruminants and other mammalians. In this investigation, we systematically reviewed the distribution of anaplasmosis among domestic ruminants in Iran. Five and four English and Persian databases were studied, respectively, based on keywords and throughout 17 years (2001–2017). Thirty-eight articles were included in this systematic review and meta-analysis. Totally, 5093 cattle, 1958 sheep, and 1232 goats corresponding to p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
12
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 19 publications
(16 citation statements)
references
References 26 publications
(47 reference statements)
1
12
0
Order By: Relevance
“…In Ukraine, the equivalent figure was 9.9% in 2015-2020. Soosaraei et al (2020) also diagnosed high heterogeneity (I 2 = 99.96%). The data of the meta-analysis showed a decrease of fascioliasis among sheep and goats in Iran.…”
Section: Discussionmentioning
confidence: 93%
See 1 more Smart Citation
“…In Ukraine, the equivalent figure was 9.9% in 2015-2020. Soosaraei et al (2020) also diagnosed high heterogeneity (I 2 = 99.96%). The data of the meta-analysis showed a decrease of fascioliasis among sheep and goats in Iran.…”
Section: Discussionmentioning
confidence: 93%
“…There, the prevalence of fasciolosis did not exceed 9.0% in cattle, 4.2% in sheep and 3.1% in goats, respectively (Khademvatan et al, 2019). Another team of scientists conducted a meta-analysis of this disease, finding the incidence to be 21.0% in cattle, 2.4% in sheep and 2.0% in goats (Soosaraei et al, 2020). The highest rates of Fasciola spp.…”
Section: Introductionmentioning
confidence: 98%
“…The ecology of different Hyalomma spp. ticks may influence the risk of tick-borne diseases in the region [ 39 , 41 , 44 46 ]. The intense animal movements across Iranian regions and neighbouring countries may also facilitate the spread of these ticks.…”
Section: Discussionmentioning
confidence: 99%
“…The current results agree with Renneker et al (10) who found that the infection rate of A. ovis in sheep of the northern areas of Iraq was 62.6%. In another study that uses PCR, Soosaraeia et al (28) and Yousefi et al (18) found that sheep and sheep and goat were infected with A.…”
Section: Discussionmentioning
confidence: 99%